2016
DOI: 10.15665/rp.v14i2.678
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Analysis of a Magnetic Circuit for Non-Destructive Testing by the Magnetic Flux Leakage Technique

Abstract: Monitoring the integrity of structures in the oil and gas industry is a mandatory task to prevent both natural disasters and economical losses. This paper presents the optimization of the geometry of a magnetic circuit for the detection of defects in pipelines by the magnetic flux leakage method. The main goal is to perform a sensitivity analysis on the geometrical parameters of the circuit to find configurations that improve the performance of the defect searching tool. The sensitivity analysis of the design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…To assess the integrity of structures, structural health monitoring (SHM) for metal members, such as pipelines in the oil and gas industry, load carrying cables in bridges, lifts, cranes, etc., is an essential task and must be done regularly to eliminate any chance of structural failure and economic loss [1]. For instance, the current transport system for oil–gas products is a pipeline which requires routine inspections due to the presence of humidity and underground pressure, because any metal losses, cracks, and corrosions may cause an accident.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the integrity of structures, structural health monitoring (SHM) for metal members, such as pipelines in the oil and gas industry, load carrying cables in bridges, lifts, cranes, etc., is an essential task and must be done regularly to eliminate any chance of structural failure and economic loss [1]. For instance, the current transport system for oil–gas products is a pipeline which requires routine inspections due to the presence of humidity and underground pressure, because any metal losses, cracks, and corrosions may cause an accident.…”
Section: Introductionmentioning
confidence: 99%
“…However, in their numerical model, an actual sensor was not simulated and, more importantly, the parameters of the sensing unit were not optimized as well. To evaluate any changes in an MFL signal caused by the geometry of the magnetic circuit, Jaimes Saavedra et al [1] performed a preliminary parametric simulation based on the MFL method. They concluded that, by increasing the thickness and reducing the length of the yoke, greater density flux leakage will be acquired.…”
Section: Introductionmentioning
confidence: 99%